Induksi Streptococcus mutans terhadap Aktivitas Proteinase Netrofil pada Degradasi Kolagen Tipe IV (Induction of Streptococcus mutans on Neutrophil Proteinase Activity in Degradation of Type IV Collagen) - Purwanto Purwanto; I Dewa Ayu Susilawati (Pustaka Kesehatan, 2014)
Background. Endothelial basal membrane of vasculature is composed mainly by type IV collagen. This vascular collagen degradation is the most powerful stimulus for platelet aggregation and thrombosis. This phenomenon is the basic mechanism of the pathogenesis of atherothrombotic diseases. Streptococcus mutans, the main bacterium of dental caries can invade easily into blood circulation, and therefore they have chance to involve in the pathogenesis of vascular destruction and thrombosis. It was assumed that S. mutans caused vascular destruction due to its potency to induce neutrophil proteinase activity to degrade type IV collagen. Objective. This study purposed to proof in vitro that S. mutans could induce and activate neutrophil proteinases leading to degradation tipe IV collagen. Methods.  Collagen degradation was analysed by means of Sodium Dodecyl Sulphate Polyacrylamid Gel Electrophoresis (SDS-PAGE) and Soluble Biotinylated Assay (SBA). Results. Results showed that S. mutans induced production and activation of neutrophil proteinases leading to type IV collagen degradation into six fragments with the molecular weight were 129; 95; 50; 32; 28; 14 kDa. Conclusion.  S. mutans induced neutrophil proteinase activity leading to degradation of type IV collagen. This study might explain one of mechanisms role of S. mutans in initiation of atherothrombotic diseases.   Key words: Streptococcus mutans; Type IV collagen; Neutrophil